Estimation of turning point location of convex solutions for nonlinear second-order differential equations - Vrabel, Robert (Mathematical Modelling and Analysis, 2012)
In this paper, we study the existence and location of turning points of the convex solutions for a certain class of the ordinary differential equations subject to the Dirichlet boundary conditions. We propose a practical and effective method for calculating the lower and upper bounds of turning point location.